Description of Participation in Daily and Social Activities for Individuals with COPD. (2nd September 2020) - Michalovic, Emilie; Jensen, Dennis; Dandurand, Ronald J.; Saad, Nathalie; Ezer, Nicole; Moullec, Gregory; Smith, Benjamin M.; Bourbeau, Jean; Sweet, Shane N.
Abstract: This study described the participation in daily and social activities and the perceived barriers and facilitators to participation of individuals with chronic obstructive pulmonary disease (COPD). Individuals, recruited from outpatient clinics, responded to a survey on their participation in, and barriers and facilitators towards, 26 daily and social activities, divided into 3 categories: (1) physical activity and movement (PAM); (2) self-care; and (3) social engagement. For each activity, chi-square analyses were used to examine participation differences by individuals': quartiles of airflow obstruction [percent predicted forced expiratory volume in 1 second (FEV1%predicted)] and breathlessness burden and exacerbation risk. Of the 200 participants (47% women; mean ± standard deviation age = 68 ± 9 years), most wanted to increase their participation in PAM activities (range 21–75%) and significant differences were found in 5/10 PAM activities for individuals' breathlessness burden and exacerbation risk (e.g., more individuals than expected in group A (modified Medical Research Council breathlessness score <2 and 0–1 exacerbations in past 12 months) participated in regular exercise as much as they wanted (χ(9) 2 =20.43, Cramer's V =.23)). Regardless of the degree of airflow obstruction or breathlessness burden and exacerbation risk, the most common barrier to participation was breathlessness ( p <.001, η 2 p =.86) and the most common facilitator was engaging as part of their routine ( p <.001, η 2 p =.75). Individuals with COPD want to increase their participation in daily and social activities but are limited by breathlessness. Strategies to alleviate breathlessness should be identified/prioritized and incorporated into individuals' daily routines to meet their self-reported participation objectives in daily and social activities.